Quantitative Analysis of Shear Texture Evolution in Accumulative Roll Bonded AA 1060 Aluminum Alloy - Peng Du; Chao Li; Lei Liu; Bao Chen; Mingyu Li; Zhijie Wang; Sha Liu (Crystals)
AA 1060 aluminum alloy underwent roll bonding with reductions of 25% and 35%, followed by accumulative roll bonding (ARB) for up to seven cycles at ambient temperature. The evolution of surface layer texture throughout the ARB process was analyzed using X-ray diffraction. Initially, the cube texture at the surface progressively transitioned to the r-cube texture throughout ARB, and the r-cube orientation intensity increases from 0 to 9.2 as the true strain accumulates. The shear texture evolution at the surface layer was quantified through mathematical formulations of texture volume fractions and accumulated true strain. The rate (dMi/dε) of cube texture reduction and r-cube texture formation are initially 15% and 20%, respectively, and they decrease rapidly with increasing cumulative true strain and then slow down to 0.6% and 0.8%. The quantitative analysis of the texture evolution used the JMAK equation, which is rarely applied in ARB studies.